The effectiveness of behavior-based safety observation program (BSOP) in the chemical manufacturing industry - Zakaria, Junaidah; Che Hassan, Che Rosmani; Hamid, Mahar Diana; Sukadarin, Ezrin Hani (Springer, 2023)
In 2022, there were 4514 reported cases of occupational accidents in Malaysian manufacturing industry, which is the highest among the sectors. Although governmental regulations mandate the use of personal protective equipment and safe working procedures, workers still take risks while completing their job. Behavioral-based safety (BBS) approach has become a reliable way for correcting workers' behavior and improving their safety performance. This article presents findings from the BBS safety intervention program and reports its effectiveness in increasing the number of workers performing safe acts. The developed program, namely BSOP (behaviorbased safety observation program), use four basic principles: (i) goal-setting, (ii) behavioral observation, (iii) constructive feedback, and (iv) reward and celebration. During execution, behavioral observation was conducted daily by appointed observers for 4 months. Results showed that the program reduced at-risk behavior (measured by the percent increase of safe acts) from 61% during baseline to 73% and 82% during the first and second behavioral observation cycles toward 14 identified targeted behavior. This study presents a comprehensive and structured process of developing safety interventions. It contributes to our understanding of the significant effects of changes in targeted behavior due to the success of the safety intervention program.